Design and fabrication of leak test rig - Yuvarajan Naidu, Thanarajan (2012)
This thesis deals with the design and fabrication of leak test rig. This thesis will discuss about leakage problems in industrial pipelines. The objective of this thesis is to design and fabricate a leak test rig. The thesis describes the approaches of designing and fabricating a leak test rig. There are numerous steps taken to design and fabricate the test rig. The structural three-dimensional solid modelling design of test rig was developed by using the Solidwork engineering drawing software. The fabrication process also undergoes many steps such as material marking, cutting, drilling, welding and grinding. In addition, it also explains the procedure of testing by the simulation of three types of common leakages which includes pinhole, pipe crack/dent and gasket leak. The testing the rig is also explained in this thesis by maintaining a pressure of 4 bars in the test rig to prove whether the test rig is functioning efficiently. Finally, the conclusion about this project is that the project objectives were achieved which was design and fabrication of a leak test rig and the recommendations for the improvement of the rig are also included together with this thesis as for instance to design and fabricate a support the leak test rig to statically hold it in place.